The Effect Of Teaching Based On Hypothetical Situations On Achievement And Critical Thinking Among Fifth-Grade Science Students (Journal of the College of Basic Education, 2026)
The current research aims to know the effect of teaching according to hypothetical situations on achievement and critical thinking amongfifth - grade science students. To verify this goal, the researchers set two null hypotheses:There are no statistically significant differences at the level of (0.05) between the average scores of the experimental group students who will study in hypothetical situations and the average scores of the control research group who study according to the traditional method in the achievement of fifth-grade science students.There are no statistically significant differences at the level of (0.05) between the average scores of the experimental group students who will study in hypothetical situations and the average scores of the control research group who study according to the traditional method in critical thinking among fifth-grade science students.To confirm the null hypotheses, the researchers conducted an experiment based on the experimental method with partial control and a post-test for two equivalent groups: the experimental group and the control group. The research sample was represented by the students of Al-Fawz Secondary School for Girls affiliated with the First Rusafa Education Directorate. The students were divided into (34, 33) One student represented the experimental group, which studied according to hypothetical situations, and the other represented the control group. Equivalence was achieved in the variables (academic achievement for the previous year, previous information, chronological age, intelligence, and critical thinking).The researchers prepared two research tools: the achievement test consisting of (40) paragraphs and the construction of a critical thinking test. They verified the psychometric properties of both tools.The experiment was implemented in the first semester, and the two researchers taught the research groups themselves. At the end of the experiment, the two independent samples were statistically analyzed, and the research results showed that the students in the experimental group outperformed the students in the control group in both critical thinking and achievement. Based on the results, the researchers made a number of recommendations and proposals.